Research Review: Psychosocial adjustment and mental health in former child soldiers – a systematic review of the literature and recommendations for future research. (12th October 2012) - Betancourt, Theresa S; Borisova, Ivelina; Williams, Timothy P; Meyers‐Ohki, Sarah E; Rubin‐Smith, Julia E; Annan, Jeannie; Kohrt, Brandon A
<x xml:space="preserve">Abstract</x> Aims and scope: This article reviews the available quantitative research on psychosocial adjustment and mental health among children (age <18 years) associated with armed forces and armed groups (CAAFAG) – commonly referred to as child soldiers. Methods: PRISMA standards for systematic reviews were used to search PubMed, PsycInfo, JSTOR, and Sociological Abstracts in February 2012 for all articles on former child soldiers and CAAFAG. Twenty‐one quantitative studies from 10 countries were analyzed for author, year of publication, journal, objectives, design, selection population, setting, instruments, prevalence estimates, and associations with war experiences. Opinion pieces, editorials, and qualitative studies were deemed beyond the scope of this study. Quality of evidence was rated according to the Systematic Assessment of Quality in Observational Research (SAQOR). Findings: According to SAQOR criteria, among the available published studies, eight studies were of high quality, four were of moderate quality, and the remaining nine were of low quality. Common limitations were lack of validated mental health measures, unclear methodology including undefined sampling approaches, and failure to report missing data. Only five studies included a comparison group of youth not involved with armed forces/armed groups, and only five studies assessed mental health at more than one point in time. Across studies, a number of risk and protective factors were associated with postconflict psychosocial adjustment and social reintegration in CAAFAG. Abduction, age of conscription, exposure to violence, gender, and community stigma were associated with increased internalizing and externalizing mental health problems. Family acceptance, social support, and educational/economic opportunities were associated with improved psychosocial adjustment. Conclusions: Research on the social reintegration and psychosocial adjustment of former child soldiers is nascent. A number of gaps in the available literature warrant future study. Recommendations to bolster the evidence base on psychosocial adjustment in former child soldiers and other war‐affected youth include more studies comprising longitudinal study designs, and validated cross‐cultural instruments for assessing mental health, as well as more integrated community‐based approaches to study design and research monitoring.